Human resources and the resource based view of the firm - Wright, Patrick M.; Dunford, Benjamin B.; Snell, Scott A. (Journal of Management, 2001)
The resource-based view (RBV) of the firm has influenced the field of strategic human resource management (SHRM) in a number of ways. This paper explores the impact of the RBV on the theoretical and empirical development of SHRM. It explores how the fields of strategy and SHRM are beginning to converge around a number of issues, and proposes a number of implications of this convergence.